KONSEP BELAJAR PERSEPEKTIF IMAM AL-GHAZALI DALAM BUKU AYYUHAL WALAD FI NASIHATI AL-MUTA'ALLIMÄªN MAW'IZATIHIM LIYA'LAMÅª WA YUMAYYIZÅª 'ILMAN NÄ€FI'AN MIN GHAYRIH - Ikmal, Hepi; Maskan, Maskan (Universitas Islam Lamongan, 2017)
Humans will not be able to utilize the natural resources such as land and sea, without armed with knowledge that qualified. Therefore, Islam then obliges Muslims to seek knowledge or learning. Learning could be capable of building a civilization. On this stand, the writer wants to discuss the thesis titled